Is smart tourism technology important in predicting visiting tourism destination? Lessons from West Java, Indonesia - Wahyu Rafdinal; Eko Susanto; Syifaa Novianti; Cahaya Juniarti (Journal of Tourism Sustainability, 2021)
This study analyzes tourist behavior in visiting tourism destinations influenced by smart tourism technology and uses the technology acceptance model (TAM) as a model for acceptance of smart tourism technology. This study used a sample of 324 tourists in West Java Province, Indonesia. Partial least square is applied to assess the relationship between smart tourism technology, perceived usefulness, perceived ease-of-use, travel intention, and visiting tourism destinations. The results of this study have revealed that the integration of TAM and smart tourism technology provides a complete explanation of the adoption of smart tourism technology. The results showed that smart tourism technology had a significant effect on perceived ease of use and perceived usefulness, and then had an effect on attitude. Travel intention was found to be directly influenced by attitude. Then, visiting tourism destinations is influenced by travel intention. By identifying smart tourism technology, various stakeholders such as the Government, tourism service providers and tourists can optimize a more comprehensive travel experience through the use of smart tourism technology. This research has developed TAM and integrated it with smart tourism technology to assess the attitudes and behavior of tourists in visiting tourism destinations.